2019
DOI: 10.7602/jmis.2019.22.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Totally Laparoscopic Total Gastrectomy versus Open Total Gastrectomy for Remnant Gastric Cancer

Abstract: This study compares the feasibility and safety of Totally Laparoscopic Total Gastrectomy (TLTG) with Open Total Gastrectomy (OTG) for Remnant Gastric Cancer (RGC) in patients who had previously undergone gastrectomy. Methods: We retrospectively collected and analyzed the data of 139 consecutive patients who underwent OTG along with 21 patients who underwent TLTG for RGC between January 2008 and December 2016. One-to-two Propensity Score Matching (PSM) was performed to compare the age, gender, body mass index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The unpredictability of abdominal pain caused by adhesions signi cantly impacts on a patient's emotions and social life, including fear for eating [41]. We assume that less exposure of the peritoneal cavity, especially the upper abdomen, may induce less adhesion around the anastomosis or provide better recovery of bowel movement [42][43][44]. Taken together, not only the possible different exposure of peritoneal cavity but also the different anastomotic technique may explain the different QoL in this study.…”
Section: Discussionmentioning
confidence: 82%
“…The unpredictability of abdominal pain caused by adhesions signi cantly impacts on a patient's emotions and social life, including fear for eating [41]. We assume that less exposure of the peritoneal cavity, especially the upper abdomen, may induce less adhesion around the anastomosis or provide better recovery of bowel movement [42][43][44]. Taken together, not only the possible different exposure of peritoneal cavity but also the different anastomotic technique may explain the different QoL in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding long-term oncological efficacy, several retrospective studies have reported comparable OS rates between the LCTG and OCTG groups 4 , 18 , 21 , 22 , 25 , 26 . However, these studies were limited by sample sizes and short follow-up durations (less than 3-year), making the results less reliable and robust for further clinical application.…”
Section: Discussionmentioning
confidence: 96%
“…The unpredictability of abdominal pain caused by adhesions significantly impacts on a patient’s emotions and social life, including fear for eating [ 46 ]. We assume that less exposure of the peritoneal cavity, especially the upper abdomen, may induce less adhesion around the anastomosis or provide better recovery of bowel movement [ 47 49 ]. Taken together, not only the possible different exposure of peritoneal cavity but also the different anastomotic technique may explain the different QoL in this study.…”
Section: Discussionmentioning
confidence: 99%